LOW FACTOR CAUSE OF HIM MOTIVATE CHILD IN GOING TROUGH LADDER EDUCATION (Case : Nagari River of Nanam District of Dale of Gumanti Sub Province of Solok) - Yulia, Fitri; Maihasni, Maihasni; Rahmat, Darmairal (Pendidikan Sosiologi, 2014)
Education represent one of the subject which it given high priority in national development. To reach the target of education one of the factor which must be paid attention is individual motivation in going through education ladder. But it seen still lower childâs motivate child in going through education ladder. The purpose of this research for the describe of childâs family background which did not continue education and any kind of low cause factor of motivate child in going through education ladder in Nagari River of Nanam District Of Dale of Gumanti Sub-Province of Solok.This Research used theory motivate David C. McCelland, with approach qualitative and descriptive research type. Technique sampling was by sampling purposive. With informan criterion, that is child desisting school when SMP and of SMA . Type Data was primary data. Teknique data collection with interview method. Unit analyse that is individual with data analysis of Miles & Huberman which consist of discount phase, presentation of data analysis or data, and withdrawal of conclusion.Result of research of shown that childâs family background which did not continue education can be seen from education of old fellow, work of old fellow, earnings of old fellow and family member amount, internal factor which cause low child motivation in going through education ladder that was lack of child enthusiasm for school, existence of past experience making low child motivation in going through education ladder, lack of willingness of child for school and learnt. Exsternal factor which caused Â lower him motivate child in going through ladder